You are on page 1of 21

.

Review of Vector Operations


.
2.
3.
4.
5.
6.
7.
8.
9.

System of Linear Equations; Matrices;


Laplace Expansion formula of Determinant;
Cramers Rule.
Dot Product, Cross Product and Determinant
Length of Vector;
Cosine formula of angle between two vectors;
Cauchys Inequality;
Component of vectors along a direction.
Equation of a plane.
Note: Even though these are included in the syllabus, but students
are assumed to know these sort of things.
1

.
Coecient Matrix of System of Linear Equations
.
Let (b1 , b2 , b3 ) R3 , and aij R (1 i 3, 1 j 3),
Consider the
following linear system of unknown (x1 , x2 , x3 ) :

a11 x1 + a12 x2 + a13 x3 = b1 ;


(*)
a21 x1 + a22 x2 + a23 x3 = b2 ;

a31 x1 + a32 x2 + a33 x3 = b3 .


.
Arrange the coecients of xi (1 i 3) as a table or matrix,
usually denoted by (aij ) as follows:

a11 a12 a13


1st row
a11 a12 a13

a
a
a
(
a
)
=
a21 a22 a23
21
22
23
ij

a
a
a
3rd row
31
32
33
a31 a32 a33

1st col.
3rd column

.
Laplace Expansion Formula of Determinant
.

a11 a12 a13


Given a 3 3-matrix (aij ) = a21 a22 a23 ,
a31 a32 a33
one can form a polynomial expression in terms of aij satisfying
certain
properties (we dont state here).
.
First, we give the rule for the signs appeared in the determinant
expression:

det(aij ) =

a11
a21
a31

= +a11
=

a12
a22
a32

a13
a23
a33

(expand along 1st row)

a22 a23
a
a
a
a
a12 21 23 +a13 21 22
a32 a33
a31 a33
a31 a32

a11 (a22 a33 a32 a23 )a12 (a21 a33 a31 a23 )

+a13 (a21 a33 a32 a23 )


= a11 a22 a33 + a13 a21 a32 + a12 a23 a31
a11 a23 a32 a12 a21 a33 a13 a22 a31 .
.

.
Laplace Expansion Formula of Determinant
.

a11 a12 a13


Given a 3 3-matrix (aij ) = a21 a22 a23 ,
a31 a32 a33
one can form a polynomial expression in terms of aij satisfying
certain
properties (we dont state here).
.
First, we give the rule for the signs appeared in the determinant
+ +
expression: +
+ +
det(aij ) =

a11
a21
a31

= +a11
=

a12
a22
a32

a13
a23
a33

(expand along 1st column)

a22 a23
a
a
a
a
a21 12 13 + +a31 12 13
a32 a33
a32 a33
a21 a23

a11 (a22 a33 a32 a23 )a21 (a12 a33 a13 a32 )

+a31 (a12 a23 a13 a21 ).


.

.
System of Linear Equations
.
Let (b1 , b2 , b3 ) R3 , and aij R (1 i 3, 1 j 3),
Consider the
following linear system of unknown (x1 , x2 , x3 ) :

a11 x1 + a12 x2 + a13 x3 = b1 ;


(*)
a21 x1 + a22 x2 + a23 x3 = b2 ;

a31 x1 + a32 x2 + a33 x3 = b3 .


.
.
Theorem: Cramers Rule for system of linear equations
.
The system (*) of equations is solvable if the following
determinant
det(aij ) does not vanish.
.
det(aij ) =

a11
a21
a31

= a11
=

a12
a22
a32

a13
a23
a33

expand along 1st row

a22 a23
a
a
a
a
a12 21 23 + a13 21 22
a32 a33
a31 a33
a31 a32

a11 (a22 a33 a32 a23 ) + a12 (a21 a33 a31 a23 )

+a13 (a21 a33 a32 a23 ).

.
System of Linear Equations
.
Theorem. Let (b1 , b2 , b3 ) R3 , and
aij R (1 i 3, 1 j 3). Suppose that the
D = det(aij ) = 0, then the following linear system

a11 x1 + a12 x2 + a13 x3 = b1 ;


(*)
a21 x1 + a22 x2 + a23 x3 = b2 ;

a31 x1 + a32 x2 + a33 x3 = b3 ,


has an unique solution (x1 , x2 , x3 ) = ( DD1 , DD2 , DD3 ), where
D1 =
.

b1
b2
b3

a12
a22
a32

a13
a23
a33

D2 =

a11
a21
a31

b1
b2
b3

a13
a23
a33

a11
a21
a31

D3 =

a12
a22
a32

b1
b2
b3

Remarks. (i) We dont have enough time to go through the theory


behind this important theorem. However, we simply state that the
proof lies in some combinatorial property of determinant, which
motivates of the creation of determinant itself.
(ii) There are cases left to be discussed, when the det(aij )
vanishes. However, it is more technical, and we would not discuss
any further.
.

.
Example. Evaluate the determinant of the matrix
1
1
1
A = (aij ) = 1 1 1 .
1
1

1
.
Solution.
det(aij ) =

a11 a12 a13


a21 a22 a23
a31 a32 a33

= a11
=

a22 a23
a
a
a
a
a12 21 23 + a13 21 22
a32 a33
a31 a33
a31 a32

a11 (a22 a33 a32 a23 ) + a12 (a21 a33 a31 a23 )

+a13 (a21 a33 a32 a23 ).


1 1
1
1 1
1 1
1 1
1 1 1 = 1
1
+1
1 1
1 1
1 1
1
1 1
= 1( (1)2 12 )1(1 1 12 ) + 1(12 (1) 1)
= 0 + 2 + 2 = 6.

.
Example.
Solve the linear system

x1 + x2 + x3 = b1 ;
(*)
x1 x2 + x3
= b2 ;

x1 + x2 x3
= b3 .
.
Let (aij ) be the associated coecient matrix of linear system (*).
D1 =

b1
b2
b3

a12
a22
a32

a13
a23
a33

b1
b2
b3

a13
a23
a33

b1
b2
b3

1
1
1

1
1
1

b1
b2
b3

1
1
1

(expand along 1st column)

1
1
1

(expand along 2nd column)

1 1
1 1
1 1
b2
+ b3
1 1
1 1
1 1
2
2
2
= ((1) (1) )b1 (1 1 )b2 + (12 (1))b3
= 2b2 + 2b3 .
= + b1

D2 =

a11
a21
a31

1 1
1 1
1 1
+ b2
b3
1 1
1 1
1 1
2
2
2
= (1 (1) )b1 + ((1) (1) )b2 (1 12 )b3
= 2b1 + 2b3 .

= b1

.
Example.
Solve the linear system

x1 + x2 + x3 = b1 ;
(*)
x1 x2 + x3
= b2 ;

x1 + x2 x3
= b3 .
.
D3 =

a11
a21
a31

a12
a22
a32

b1
b2
b3

1
1
1

1
1
1

b1
b2
b3

(expand along 2nd column)

= (1
+ ((1)2 12 )b3
= 2b1 + 2b2 .
It follows from the Cramers rule that the solution vector
(
)
D1 D2 D3
(x1 , x2 , x3 ) =
,
,
D D D
(
)
2b2 + 2b3 2b1 + 2b3 2b1 + 2b2
=
,
,
4
4
4
(
)
b2 + b3 b1 + b3 b1 + b2
=
,
,
.
2
2
2
Remark. This solution can be easily obtained by adding any two
equations, and then simplify a little bit.
2

(1))b1 (1 (1)2 )b2

. Dot Product, Cross Product and Determinant


Let a = (a1 , a2 , a3 ) = a1 i + a2 j + a3 j, b = (b1 , b2 , b3 ) =
b1 i + b2 j + b3 k, and c = (c1 , c2 , c3 ) = c1 i + c2 j + c3 k,
where { i = e1 , j = e2 , k = e3 } is the canonical basis of R3 .
.
a b =< a, b >= a1 b1 + a2 b2 + a3 b3 , and
i
j k
a a
a a
a a
a b = a1 a2 a3 = 2 3 i 1 3 j + 1 2 k.
b2 b3
b1 b3
b1 b2
b1 b2 b3
.
.
Example.
Evaluate the dot product (1, 2, 3) (4, 5, 6).
.
Solution. (1, 2, 3) (4, 5, 6) =< (1, 2, 3), (4, 5, 6) >
= 1 4 + 2 5 + 3 6 = 4 + 10 + 18 = 32.
.
Example.
Evaluate the cross product (1, 2, 3) (4, 5, 6).
.
( 2 3
)
1
3
1
2
Solution. (1, 2, 3) (4, 5, 6) =
5
6 , 4
6 , 4
5
= ( 12 15, (6 12), 5 8, ) = ( 3, 6, 3).
.

.
Example. Prove that det(a, b, c) = (a b) c for any
3
.a, b, c R .
Solution.

a 1 b1 c1
det(a, b, c) = a2 b2 c2
a 3 b3 c3

(expands along the 3rd column)

a a
a a
a a
= c1 2 3 c2 1 3 + c3 1 2
b2 b3
b1 b3
b1 b2
)
(
a2 a3
a1 a3
a1 a2
=
,
,
( c1 , c2 , c3 )
b2 b3
b1 b3
b1 b2
= (a b) c.
.
Exercise. Prove the following equalities:
det(a, b, c) =
.

det(b, c, a) =

det(c, a, b)

= det(b, a, c) = det(a, c, b) = det(c, b, a).


.

. Properties of Determinant
.
Let a1 , a2 , , an be vectors in Rn , and denote
aj = ( a1j , a2j , , anj ) with n components,
vertically
vector:
as column

a11 a12
a1j
a2j
a21 a22

aj = . ,
det(aij ) = .
..
..
..
.

by
and we write it
a1n
a2n
.. .
.

anj
an1 an2 ann
.
.
Write the polynomial expression det(aij ) = det(a1 , a2 , , an ),
then the determinant polynomial satises the following:
1. (Normalization): det(e , e , , e ) = 1.
1 2
n
. (Skew-symmetric)
By interchanging any two columns, det changes by 1 :
det(a1 , , ai , , aj , , an )
= det(a1 , , aj , , ai , , an ) with i < j.

.
Orthogonality of Cross-Product
.
Let a, b R3 , the cross-product a b satises the following:
1. a b = b a;
.

. < a b, a >=< a b, b >= 0.

Solution. (1) This is just a matter of checking.


(2)(< a b, a >
)
a2 a3
a a
a a
=
, 1 3 , 1 2
(a1 , a2 , a3 )
b2 b3
b1 b3
b1 b2
a a
a a
a a
= a1 2 3 a2 1 3 + a3 1 2
b2 b3
b1 b3
b1 b2
= a1 (a2 b3 a3 b2 ) a2 (a1 b3 a3 b1 ) + a3 (a1 b2 b1 a2 )
= 0.
.
Remark. In fact, it follows from the skew-symmetric property (*)
of determinant det that

< a b, a >= det(a, b, a) = det(a, b, a) = < a b, a >,


.so 2 < a b, a >= 0.
.

.
Let u, v, w R3 and , R, then
1. < u, v >=< v, u >;
2. < u + v, w >= < u, w > + < v, w >;
3. < w, u + v >= < w, u > + < w, v >;
. < v, v > 0 for all v R3 ;
5. < v, v >= 0 if and only if v = 0.
4

.
.

Denition. Dene v = < v, v >, which is usually called the


length
of the vector v.
.
In the distance we will prove that
.
1. v = | | v;
2. |v 0 for all v R3 ; and v = 0 if and only if v = 0.
3. u + v u + v, and equality holds if and only if u and
v are in the same direction, i.e. there exists , 0 but not
both zero such that u = v.
.
.

.
Prove
that (< a, b >)2 + a b2 = a2 b2 .
.

()

Proof. The result is just an algebraic identity. Recall that


a a
a a
a a
a b = 2 3 i 1 3 j + 1 2 k. Then
b2 b3
b1 b3
b1 b2

| < a, b > |2 + a b2
= (a1 b1 + a2 b2 + a3 b3 )2
+(a2 b3 b2 a3 )2 + (a1 b3 b1 a3 )2 + (a1 b2 b1 a2 )2
= (a2 b3 )2 + (b2 a3 )2 + (a1 b3 )2 + (b1 a3 )2 + (a1 b2 )2 + (b1 a2 )2
+(a1 b1 )2 + (a2 b2 )2 + (a3 b3 )2
= (a21 + a22 + a23 )(b21 + b22 + b23 ) = a2 b2 .

.
By (*), a2 b2 = | < a, b > |2 + a b2 | < a, b > |2 ,
so a b | < a, b > |. Hence, if a and b are non-zero
< a, b >
1.
vectors, then

.
.

< a, b >
1.
Recall that if a and b are non-zero vectors, then
a b
.
Denition. Let u and v be non-zero vectors in R3 . The (directed)
the vectors
u and v is given by
angle (u, v) between
(
)
<
u,
v
>
(u, v) = cos1
.
u v
.
Then < u, v >= u v cos (u, v)
| < u, v > |2 = u2 v2 cos2 (u, v).
By identity (< u, v >)2 + u v2 = u2 v2
.
.u v = u v sin (u, v).
Proof. u2 v2 sin2 (u, v)
= u2 v2 ( 1 cos2 (u, v) )
= u2 v2 u2 v2 cos2 (u, v)
= u2 v2 (< u, v >)2

= u v2 .
So u v = | < u, v > | sin (u, v).

(), we have

.
Denition. Let u, v be vectors in R3 . u and v are perpendicular, if
.< u, v >= 0. Recall < u, v >= u v cos (u, v).
.
Proposition. Two vectors are perpendicular if
(
. u, v) = /2, or u = 0, or v = 0.
.
Example. Let a, b R3 , then the vector a b is perpendicular to
.both a and b.
Remark. Even though a and b are non-zero, the cross-product
a b may be zero. According to a b = a b sin (a, b),
it happens if and only if sin (a, b) = 0, i.e. they are in the same
direction, or they are in the opposite direction.

.
Cauchys Inequality. Let u = (x1 , x2 , x3 ), v = (y1 , y2 , y3 ) R3 .
2
2
2
.Prove that |u v| u v .
Proof. u2 v2 |u v|2

= (x21 + x22 + x23 )(y21 + y22 + y23 ) (x1 y1 + x2 y2 + x3 y3 )2


= x21 y21 + x22 y21 + x23 y21 + (x21 y22 + x22 y22 + x23 y22 ) + x21 y23 + x22 y23 + x23 y23
(
)
(x1 y1 )2 + (x2 y2 )2 + (x3 y3 )2 + 2x1 y1 x2 y2 + 2x2 y2 x3 y3 + 2x3 y3 x1 y1
= (x1 y2 x2 y1 )2 + (x1 y3 x3 y1 )2 + (x3 y2 x2 y3 )2 0.
In general, we have
.
Cauchys Inequality in Rn
.
Let a = (a1 , a2 ,
, an ), b
= (b1 , b2 , , bn ) Rn , then
| < a, b > | ni=1 a2i ni=1 b2i .
a1
a2
an
Equality holds if and only if
=
= = .
b
b
bn
1
2
.
.

.
Denition. Let u be a non-zero vector in R3 , and v R3 .
Dene the component compu v of v in the direction given by u to
<v,u>
be compu v = <
u,u> u.
.
With this denition, we have the following result:
.
Proposition. Let u be a non-zero vector in R3 , and v, w R3 .
Then (i) compu (v + w) = compu v + compu w.
(ii) compu (v) = compu (v) for all R;
(iii)
The vector v compu v is is perpendicular to the vector u.
.
Proof. (i) and (ii) follows directly from the formula of compu v.
(iii) < v compu v, u >=< v, u > < compu v, u >
< v, u >
=< v, u > <
u, u >
< u, u >
< v, u >
=< v, u >
< u, u >
< u, u >
=< v, u > < v, u >= 0.
Hence v compu v and u are perpendicular.
.

.
Denition. A non-zero vector n = (, m, n) is called a normal

vector to the plane , if n is perpendicular to the any vector QR,


.where Q, R are any two points on the plane .
Given a point P(x0 , y0 , z0 ) in R3 , and a (non-zero) direction vector
n = (, m, n) geometrically one can construct a plane in space
R3 passing through the given point P with normal vector n.
However, we want to give the equation of the plane in terms of
P(x0 , y0 , z0 ) and n = (, m, n).
Let Q(x, y, z) be any arbitrary point on the plane , then

PQ = (x x0 , y y0 , z z0 ). It follows from n normal to that

n = (, m, n) PQ = (x x0 , y y0 , z z0 ), i.e.

0 = < n, PQ >

= < (, m, n), (x x0 , y y0 , z z0 ) >


.
Proposition. =
P(x,(
y,xz
) lies
the
x0 ) on
+m
(y plane
y0 )
+ ifn(and
z zonly
0 ). if (x, y, z)
satises
the
equation
(
x

x
)
+
m
(
y

y
)
+
n
(
z
z0 ) = 0.
0
0
.
.

.
Let be the plane passing through A(a1 , a2 , a3 ), B(b1 , b2 , b3 ) and
C(c1 , c2 , c3 ). Then for any point P(x, y, z) of , one has
.x + my + nz = D, where (, m, n) is normal to the plane .

Solution. Let b = AB = OB OA = (b1 a1 , b2 a2 , b3 a3 ),

and c = AC = OC OA = (c1 a1 , c2 a2 , c3 a3 ).
Let P(x, y, z) be any point on the plane , then

AP = OP OA = (x a1 , y a2 , z a3 ).
Then the vector n = b c = (, m, n) is perpendicular to the

plane, i.e. n AP, hence

0 =< n, AP >=< b c, AP, >= det(b, c, AP)


x a1 y a2 z a3
(expand along 1st row)
= b1 a1 b2 a2 b3 a3
c1 a1 c2 a2 c3 a3
=< (, m, n), (x a1 , y a2 , z a3 ) >
= (x a1 ) + m(y a2 ) + n(z a3 ) + D = x + my + nz + D,
where D R.
.

You might also like